What Is Wrong with Taylor Rules? Using Judgment in Monetary Policy through Targeting Rules - Svensson, Lars E. O (Journal of Economic Literature, 2003)
It is argued that inflation targeting is best understood as a commitment to a targeting rule rather than an instrument rule, either a general targeting rule (explicit objectives for monetary policy) or a specific targeting rule (a criterion for (the forecasts of) the target variables to be fulfilled), essentially the equality of the marginal rates of transformation and substitution between the target variables. Targeting rules allow the use of judgment and extra-model information, are more robust and easier to verify than optimal instrument rules, and they can nevertheless bring the economy close to the socially optimal equilibrium.